The nomenclatural status of Rana gaimardii Bory de Saint-Vincent, 1828, and Hyla quoyi Bory de Saint-Vincent, 1828 (Anura, Hylidae) - Caramaschi, Ulisses; de Niemeyer, Helianne (Zootaxa, 2010)
The nomenclatural status of Rana gaimardii Bory de Saint-Vincent, 1828, and Hyla quoyi Bory de Saint-Vincent, 1828 (Anura, Hylidae) are discussed. Rana gaimardii and its combination Hyla gaimardi, a nomen oblitum under Article 23.9.1 of the International Code of Zoological Nomenclature, may be removed from the synonymy of Hypsiboas boans (Linnaeus, 1758) and included in the synonymy of Hypsiboas faber (Wied-Neuwied, 1821) to improve the geographic distribution of both species. Hyla quoyi Bory de Saint-Vincent, 1828, considered by Frost (2010) as incertae sedis in the Hylinae and as a nomen oblitum under the Article 23.9.1 of the International Code of Zoological Nomenclature, if available would replace the well established name Hypsiboas prasinus (Burmeister, 1856); therefore, to improve the nomenclatural status of both species, Hyla quoyi must be included in the synonymy of H. prasinus as a nomen oblitum. Hypsiboas prasinus is a nomen protectum relative to Hyla quoyi, a nomen oblitum.